2017
DOI: 10.1080/16506073.2017.1388276
|View full text |Cite
|
Sign up to set email alerts
|

Individually tailored internet-based cognitive behaviour therapy for older adults with anxiety and depression: a randomised controlled trial

Abstract: Mixed anxiety and depression is common among older adults. The aim of the study was to compare the effects of an eight-week-long tailored internet-supported cognitive behaviour therapy (ICBT) programme and to compare against the provision of weekly general support. A second aim was to investigate if pre-treatment cognitive flexibility and self-reported cognitive problems would predict outcome. We included 66 older adults (aged over 60 years) with mixed anxiety/depression following media recruitment and randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 52 publications
3
32
0
1
Order By: Relevance
“…However, another study, conducted on 66 older adults with mixed anxiety depression randomized to ICBT or control conditions, who were administered the WCST (perseverative errors) and the Cognitive Failures Questionnaire before treatment, reported a moderate between‐group effect on the main outcome measure, the Beck Anxiety Inventory (d=0.50), favoring the treatment group. The authors concluded that the role of cognitive functioning in the outcome of ICBT should be further investigated.…”
Section: Mechanisms Of Change and Predictors Of Outcomementioning
confidence: 99%
“…However, another study, conducted on 66 older adults with mixed anxiety depression randomized to ICBT or control conditions, who were administered the WCST (perseverative errors) and the Cognitive Failures Questionnaire before treatment, reported a moderate between‐group effect on the main outcome measure, the Beck Anxiety Inventory (d=0.50), favoring the treatment group. The authors concluded that the role of cognitive functioning in the outcome of ICBT should be further investigated.…”
Section: Mechanisms Of Change and Predictors Of Outcomementioning
confidence: 99%
“…This also saves time. However, sometimes we need to recruit participants in several waves and it is not always easy to recruit for example older persons ( Silfvernagel et al, 2018 ). But often the sample sizes tend to be around 80–120 participants, and one trend in ICBT research is to view smaller controlled trials as “pilots” ( Lundgren et al, 2016 ), instead of running small open trials as the pilot.…”
Section: Short-term Effectsmentioning
confidence: 99%
“…Third, cognitive function could potentially influence the outcome of internet interventions, for example in older adults, but also in persons with depression which is known to influence cognition ( Gotlib and Hammen, 2009 ). We have studied executive function in association with clinical trials and whereas most studies have shown no effects ( Andersson et al, 2008b ; Lindner et al, 2016 ), we did recently find an association between perseverative errors and negative outcome in a study on ICBT for older adults ( Silfvernagel et al, 2018 ).…”
Section: Predictors Of Outcome and Mechanisms Of Changementioning
confidence: 99%
“…Both collaborative care, CGA and stepped-care models give attention to the complex multifactorial etiology of depressiveness. This is also the case in CBT in so called tailored interventions [118] and in augmentation strategies in pharmacology [119,120].…”
Section: Treatment Of Depressiveness In Very Old Personsmentioning
confidence: 98%